2016
DOI: 10.1111/nph.14302
|View full text |Cite
|
Sign up to set email alerts
|

A core function of EDS1 with PAD4 is to protect the salicylic acid defense sector in Arabidopsis immunity

Abstract: Plant defenses induced by salicylic acid (SA) are vital for resistance against biotrophic pathogens. In basal and receptor-triggered immunity, SA accumulation is promoted by Enhanced Disease Susceptibility1 with its co-regulator Phytoalexin Deficient4 (EDS1/PAD4). Current models position EDS1/PAD4 upstream of SA but their functional relationship remains unclear. In a genetic and transcriptomic analysis of Arabidopsis autoimmunity caused by constitutive or conditional EDS1/PAD4 overexpression, intrinsic EDS1/PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
280
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(292 citation statements)
references
References 88 publications
(167 reference statements)
12
280
0
Order By: Relevance
“…This property highlights a possible intersection between the drought responsive ASTRAL genes and immunity. Both NDR1 and CCRPW8 mediated signalling converge in triggering increase in SA, which appears to be maintained in the aquatic species in our study (83).…”
supporting
confidence: 58%
“…This property highlights a possible intersection between the drought responsive ASTRAL genes and immunity. Both NDR1 and CCRPW8 mediated signalling converge in triggering increase in SA, which appears to be maintained in the aquatic species in our study (83).…”
supporting
confidence: 58%
“…Previous studies have shown a differential requirement for defence phytohormones in CNL-mediated ETI in Arabidopsis (Tsuda et al, 2009;Maekawa et al, 2012;Cui et al, 2017). In quadruple mutant plants that simultaneously lack ET, jasmonic acid (JA) and SA signalling, designated deps (dde2 ein2 pad4 sid2), RPS2-mediated pathogen growth restriction was impaired by 80%, whereas RPM1-or MLA1-mediated immunity was largely retained (Tsuda et al, 2009;Maekawa et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…The fact that EDS1 solely controls the accumulation of a pool of proteins with antagonistic roles illustrates the need for a homeostatic mechanism to control the extent of SAR. Although signaling from the EDS1/PAD4 hub can work independently of SA, (Cui et al, ), its role in promoting SA‐mediated basal resistance has been extensively reported (Rietz et al, ). In line with the observed upregulation of SA‐associated proteins, prt1‐1 leaves infected with Pst DC3000 showed slightly increased levels of SA compared to WT (Figure a).…”
Section: Resultsmentioning
confidence: 99%